Re-thinking initiative of the Egyptian Jamaʿa Islamiyya in 1997 - Niaz, Maissa Hussein (AUC Knowledge Fountain, 2016)
The rising worldwide danger of Islamist militancy arouses the need for the search of solutions for the containment of this danger at a highest priority. This thesis examines the case of the successful violence-ending experience of the Egyptian Jamaʿa Islamiyya (EJI), being a model for conflict resolution with the political regime and an example of the possible de-radicalization of one of the most militant Islamist groups in the modern history of Egypt. The study focuses on the Renouncing - Violence Initiative that was issued by EJI in 1997 and the subsequent issuing of a “Correction of Conceptions Series” that aimed to refute all previously held violence doctrines by the EJI, and those currently held by other militant Islamist groups. In order to do so, the study will attempt to analyze the factors that led to the transformation of that group to the moderate and even reformist path. The backgrounds on the emergence and behavioral evolution of the EJI will be reviewed, in addition to the violence legitimizing doctrines followed by the analysis of the new de-legitimizing violence literature. The thesis concludes that the occurrence of such de-radicalizing incident opens the prospects for other initiatives to occur, given that required conditions and appropriate frameworks are provided.